Organizational Culture’s Impact on Life Satisfaction through Professional Exhaustion and Motivation Among XXX Hospital Employees - Hengky Siswanto; Rina Anindita; Tjipto Rini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Healthcare professionals are vulnerable to professional burnout and decreased motivation. In addition to these two things, life satisfaction is also an important aspect that needs attention. An important factor that influences professional burnout, employee motivation and life satisfaction is organizational culture. Organizational culture as a value system believed by all members of the organization, which is learned, applied and developed continuously, functions as an adhesive system, and can be used as a reference for behavior in the organization to achieve organizational goals that have been implemented. This study aims to analyze the effect of Organizational Culture on Life Satisfaction through professional burnout, and employee motivation as intervening variables in XXX Hospital. This research method is quantitative explanatory research. The sample in this study were health professionals of XXX Hospital totaling 74 respondents. Data collection using questionnaires and analysis techniques using SEM-PLS through the SmartPls application.The results showed that Organizational Culture directly and indirectly affects life satisfaction through professional burnout, and employee motivation as an intervening variable in health professionals at XXX Hospital. These results in theoretical implications support the theory and previous research. Managerially, it is expected to provide input for XXX Hospital management to strengthen organizational culture. These efforts can help reduce the level of professional burnout, increase employee motivation and ultimately increase the life satisfaction of health professionals. There is an influence of organizational culture on professional burnout, employee motivation and life satisfaction in healthcare professionals at XXX Hospital.